Circulation of the representatives of acute respiratory viral infections and influenza viruses in Kazakhstan (Experimental biology, 2018)
Acute respiratory viral infections (ARVI) and influenza remain one of the most urgent medical and social-economic problems throughout the world, including Kazakhstan. In this article the data of the long-term dynamics of the incidence of influenza and ARVI rates in the Kazakhstan for 2000-2001 to 2016-2017, data of epidemiological monitoring of the circulation of influenza viruses in the influenza season 2016-2017 are analyzed. The described 2016-20 influenza season was characterized by a relatively earlier onset – the maximum incidence of ARI was observed at 50 on 2016 y. (118.9 per 100 thousand population) and at 02 weeks on 2017 y. (192.7 per 100 thousand population). PCR diagnostics established the circulation of influenza A viruses H3N2 and B and the onset of the epidemic season (44 ISSN 1563-0218 Experimental Biology. №2 (75). 2018 157 Табаева А., Картпаева Б. weeks) was associated with a greater activity of the influenza B virus, and its completion was dominated by influenza A H3N2 virus (week 18). A distinctive feature of the season was the absence of the influenza A virus H1N1 pdm09. Genetic analysis of isolated strains of influenza showed their similarity with vaccine strains A/Hong Kong/4801/2014 and B/Brisbane/60/2008. Sequencing of the studied strains of the influenza virus demonstrated the preservation of their sensitivity to antiviral drugs.Key words: influenza viruses, PCR, genetic analysis, sequencing, sensitivity to antiviral drugs, seasonal incidence of influenza, seasonal incidence of ARVI.